Micropropagation of young inflorescence Curcuma hybrid In vitro - Yoosumran, V.; Saetiew, K.; Ruamrungsri, S.; Akarapisarn, A.; Teerarak, M. (My University, 2022)
Five cultivars of curcuma hybrid consisted of 3 Paracurcuma and 2 Eucurcuma young inflorescences were cultured on MS medium supplemented with 0, 0.5 and 1 mg/l NAA and BA for 8 weeks. It was found that young inflorescences Paracurcuma hybrid Curcuma ‘Yuki’ cultured on MS medium supplement with the 1 mg/l NAA and 0.5 mg/l BA were able to induce the most shoots at 2.67 shoots, with the highest percentage of shoots (80.00%) and the average plant height is 5 cm. For Curcuma ‘Burgundy’ and Curcuma ‘Phonphisit’ cultured on MS medium supplement with 1 mg/l NAA and 1 mg/l BA, they were able to induce the most shoots at 1.66 and 1.78 shoots, the highest percentage of shoots is 73.33 and 76.67% respectively and the average plant height is 5 cm. The other cultivars Eucurcuma consist of Curcuma ‘Sweetmemory’ and Curcuma ‘Banrai Red’. The young inflorescences were divided into 2 parts, the upper and the lower one. The result shows that the lower shoot induction is better than upper one. Curcuma ‘Sweetmemory’ grown on MS medium supplemented with 0.5 mg/l NAA and 0.5 mg/l BA were able to induce the most shoots at 2.38 shoots, and the highest percentage of shoots is 83.33%. Curcuma ‘Banrai Red’ grown on MS medium supplemented with 0.5 mg/l NAA and 1 mg/l BA were able to induce the most shoots at 1.98 shoots, the highest percentage of shoots is 63.33% and both cultivars were the same height average at 5 cm.
Keywords: Eucurcuma; micropropagation; Paracurcuma